Psychological Insights into Human Resource Management Strategy: A Qualitative Exploration and Review of Literature - Asriati, A. (Manunggal Halim Jaya, 2025)
This study explores the integration of psychological insights into human resource management (HRM) strategies, examining its implications for recruitment and selection, training and development, performance management, and organizational culture. The research aims to elucidate the mechanisms through which psychological principles influence HRM practices and to examine the role of cultural diversity in shaping the effectiveness of HRM strategies. A multi-level perspective is adopted, considering individual, group, and organizational factors in shaping HRM outcomes. The study employs a comprehensive literature review methodology, synthesizing findings from diverse sources to provide insights into the complex interplay between psychology and organizational practices. Key findings highlight the importance of personality assessment, cognitive abilities, cultural fit, and emotional intelligence in recruitment and selection processes. Additionally, the study underscores the significance of adopting a learner-centered approach to training design and the role of positive feedback interventions in enhancing performance management practices. Furthermore, the research emphasizes the pivotal role of leadership in shaping organizational culture and driving cultural change. The study contributes to advancing theoretical understanding and informing evidence based HRM practices.